TI_GERICHTE 12.2023.5 vom 4. April 2023 , Mediazione "rent to buy" - diritto alla mercede - riduzione di una mercede eccessiva - TI Tribunale d'appello (2023)
Mediazione "rent to buy" - diritto alla mercede - riduzione di una mercede eccessiva